Synthesis of Viscoelastic Behavior Through Electromechanical Coupling - Kuhnert, Willian M. [UNESP] (2020)
Background: Viscoelasticity is a property of materials that present elastic and viscous behavior when they experience deformation. The simplest model that can represent the viscoelastic behavior is generally called the Standard Linear Solid model or Zener model. Purpose: Based on the Zener model, the objective of this paper is to present the concept and the design of equivalent electromechanical systems that permit the emulation of viscoelastic behavior. Besides, the possibility of harvesting the energy normally wasted as heat in viscoelastic materials is also considered. Methods: The methods applied in this paper are based on the analytic development of equations in time and frequency domain, including optimization and numerical simulations. Results: Equivalent equations were derived considering the mechanical and electromechanical analogy. These equations were verified by correlating known results from the literature. New results for white noise excitation were obtained and optimization of power harvesting was performed. Conclusions: The proposed electromechanical system is equivalent to the Zener system if its mechanical damping is small when compared to the equivalent electrical damping effect. Resulting in viscoelastic behavior without the need of viscoelastic materials, electromechanical equivalent Zener systems also allow energy recovery whilst maintaining vibration isolation.